Determination of selected biochemical parameters in blood serum and egg quality of Czech and Slovak native hens depending on the housing system and hen age - Kraus, Adam; Zita, Lukáš; Krunt, Ondřej; Härtlová, Helena; Chmelíková, Eva (Poultry science, 2021)
The objective of this study was to determine and evaluate the impact of the age and housing system on blood indicators (triacylglycerides, total cholesterol, aspartate aminotransferase, total proteins, albumin, glucose) and physical egg quality parameters (egg weight, shape index and surface area, eggshell proportion, thickness, strength, and color, albumen proportion and index, Haugh units, yolk proportion, index and yolk-to-albumen ratio) in selected native breeds of the Czech Republic (the Czech Golden Spotted hens) and Slovakia (the Oravka hens). Furthermore, the concentration of cholesterol in the yolk was determined. A total of 132 animals were used. There were 60 eggs collected from each breed at each monitored period for the evaluation of egg quality. Blood samples were taken by puncture of a wing vein. The assessments were made when the hens were of 34, 42, and 50 weeks old. Enriched cages and floor pens with litter were used as housing systems. The effects of breed, housing system, and age were observed. Furthermore, interactions among these factors were calculated. The significant effect of housing system was found in total cholesterol (P = 0.098) and aspartate aminotransferase (P = 0.0343) and the significant effect of age in total protein (P = 0.0392). The significant effect of breed (P = 0.0199), housing system (P = 0.0001), and age (P = 0.0001) was found in concentration of cholesterol in the yolk. Regarding the egg quality, the significant effect of breed (P = 0.0001) was found in eggshell color, albumen index and Haugh units, whereas the significant effect of housing system was found in egg weight (P = 0.0002), egg surface area (P = 0.0003), eggshell proportion (P = 0.0460), thickness (P = 0.0216), strength (P = 0.0049), and color (P = 0.0009). The significant effect of age was determined in all parameters except for the eggshell proportion and strength. The results represent an interesting comparison of changes in biochemical blood and egg quality parameters. It is necessary to further evaluate these indicators, especially in other genetic resources of hens, where the data are often nonexisting.
Keywords: Chickens; Cholesterol; zvířata; Female; Serum; Slovakia; bydlení zvířat; Slovenská republika; Eggs; Česká republika; Aging; blood serum; vaječný žloutek; Animals; Egg Yolk; Ovum; ženské pohlaví; native breed; Czech Republic; vejce; sérum; stárnutí; kur domácí; cholesterol; Housing, Animal; egg quality; age; Egg Shell; vaječná skořápka; housing system; ovum